Post-traumatic growth experience of first-line emergency nurses infected with COVID-19 during the epidemic period—A qualitative study in Shanghai, China - Jiang, Jinxia; Han, Peng; Huang, Xiangdong; Liu, Yue; Shao, Haiyan; Zeng, Li; Duan, Xia (Frontiers in Public Health, 2022)
Background In March 2022, Shanghai, China, was hit by a severe wave of SARS-CoV-2 transmission caused by the Omicron variant strain. The medical staff was greatly infected during this period, which posed a traumatic event for them. Meanwhile, they also experience post-traumatic growth under introspection and positive change. However, the psychological coping and growth after infection with COVID-19 among medical staff have rarely been investigated. Objectives To explore the process and influencing factors of post-traumatic growth among emergency nurses infected with coronavirus disease (COVID-19) so as to provide a new perspective and theoretical basis for psychological rehabilitation or intervention for medical staff who experienced traumatic events. Methods The study used a qualitative design based on the phenomenological approach. A purposive sampling method was used to explore the subjective feelings and post-traumatic growth among 13 first-line emergency nurses infected with COVID-19 in Shanghai, China. Semi-structured face-to-face interviews were conducted in June 2022. A Seven-step Colaizzi process was used for data analysis. Results Themes were described and extracted from the experience and insights at different stages during the fight against the virus. Three main themes, i.e., stress period, adjustment period, and growth period, as well as several sub-themes, were identified. Conclusion First-line emergency nurses infected with COVID-19 are a sensitive group that should be given more attention. Investigating how they achieve psychological adjustment and growth in the case of severe trauma can provide valuable references for nursing management and education in the future. Society, hospital and nursing managers should pay more attention to the PTG of nurses and establish supportive PTG strategies, which will benefit the retention rate and career development of nurses.